2007
DOI: 10.1111/j.1365-2672.2006.03117.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaCl and KCl on fate and growth/no growth interfaces of Listeria monocytogenes Scott A at different pH and nisin concentrations

Abstract: Aims:  The fate of Listeria monocytogenes Scott A, was studied in broth, at different aws (by adding NaCl or KCl from 0·0 to 1·4 mol l−1), pHs (from 4·0 to 7·3 by adding lactic acid), and nisin concentrations (from 0 to 100 IU ml−1). Methods and results:  Increasing salt and nisin concentrations and decreasing pH resulted in lower growth rates and extended lag phases. At pH 4·5 no growth was observed while in presence of nisin and/or 1 mol l−1 salts of both kinds, L. monocytogenes Scott A was inactivated. Equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 42 publications
6
38
2
3
Order By: Relevance
“…An equivalent reduction in a w to that achievable by salt addition was obtained by addition of KCl. A range from 0 to 1.4mol NaCl and KCl was added and in both cases a w was reduced from 0.999 to ~0.950 [26]. Other salt replacers used include other potassium salts, calcium chloride, magnesium sulphate and metal ions [71].…”
Section: Reduction or Replacement Of Salt In Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An equivalent reduction in a w to that achievable by salt addition was obtained by addition of KCl. A range from 0 to 1.4mol NaCl and KCl was added and in both cases a w was reduced from 0.999 to ~0.950 [26]. Other salt replacers used include other potassium salts, calcium chloride, magnesium sulphate and metal ions [71].…”
Section: Reduction or Replacement Of Salt In Foodsmentioning
confidence: 99%
“…In food, L. monocytogenes is capable of growing in cabbage juice containing 5% salt [24], survival was detected in a 30% brine solution stored for > 60 days and in beef immersed in a 22% salt solution stored for 100 days [25]. Lowering a w of the growth media by the addition of salt creates an unfavourable environment for L. monocytogenes, which leads to reduced growth rates, extended lag phases and overall population decline [26]. Growth of L. monocytogenes has been observed at a w of 0.90 in TSB with added salt, and survival has been reported at an a w of 0.83 [25].…”
Section: Effects Of Salt On Bacteriamentioning
confidence: 99%
“…This Gram-positive pathogen has the ability to survive under a wide range of conditions such as refrigeration temperatures (2e4 C), acidic pH and high salt concentrations (up to 10 g/100 g) in foods (Gandhi & Chikindas, 2007). Control of L. monocytogenes in various foods usually includes the application of 'hurdle' technology by combining factors such as low temperature, acidification, low a w and chemical or natural preservatives (Boziaris, Skandamis, Anastasiadi, & Nychas, 2006;Hill, Cotter, Sleator, & Gahan, 2002;Valero et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The use of salt as a method for food preservation has been well established (Desmond, 2006;Guinee & Fox, 2004). Boziaris et al, (2007) found that salt had a slightly inhibitory affect on bacteria especially at initial exposure but after adaptation, salt may actually stimulate bacterial growth. In contrast to the noted salt tolerance of Listeria spp, Conner et al, (1986) found that cabbage juice containing 1% salt caused an initial decrease in populations of Listeria.…”
Section: Discussionmentioning
confidence: 99%